Severity and frequency of concussion symptoms in female athletes in Iceland - Signý Benediktsdóttir 1999- (2021)
Participating in sports is a risk factor for sustaining a concussion. Research has demonstrated that female athletes are at greater risk of experiencing worse concussion symptoms than male athletes. However, symptoms associated with concussions are non-specific and therefore present among populations that have not sustained concussions. The primary purpose of this study was to compare the severity and frequency of current concussion symptoms among female athletes with a history of concussions to female athletes with no history of concussions. A total of 70 female athletes participated in the study, 26 participants had a history of concussions, and 44 participants had no history of concussions. Participants answered the SCAT-5 concussion symptom list during semi-structured interviews. Symptom severity scores and frequency of reported symptoms was compared between the groups using independent t-tests. Participants with a history of concussion had significantly higher symptom severity scores than participants with no concussion history. Also, all current concussion symptoms were more frequent in the concussion group then the no concussion group. More participants in the concussion group reported worsening of symptoms with mental and physical activity. Keywords: Concussion symptoms, symptom severity, female athletes Fyrri rannsóknir hafa sýnt að þátttaka í íþróttum er áhættuþáttur fyrir að hljóta heilahristing. Þá hafa rannsóknir einnig bent til þess að konur í íþróttum séu í meiri hættu á að finna fyrir verri einkenum í kjölfar heilahristings en karlar í íþróttum. En einkenni heilahristings eru ósérstæk og eru þess vegna til staðar hjá hópum sem ekki hafa hlotið heilahristing. Markmið rannsóknarinnar var að bera saman alvarleika og fjölda heilahristingseinkenna hjá íþróttakonum sem hafa fengið heilahristing og sem hafa ekki fengið heilahristing. Fjöldi þátttakenda í rannsókninni voru 70 íþróttakonur, þar af voru 26 sem höfðu fengið heilahristing og 44 sem höfðu aldrei fengið ...